Extração e aplicação de óleos essenciais como metodologia no ensino de química orgânica - Vieira, Diego Leonidas Esplendo (2023)
The application of active methodologies in basic education is recent, and when used in a balanced way and adapted to the individual and collective context of students, it is of great importance for teaching. In teaching chemistry, it is noticed that students cannot learn because they cannot associate the content studied with its social context, thus losing interest in the subject explained. This indicates that this teaching is being done out of context. This work aimed to develop and analyze the application of a sequence of theoretical and experimental classes, providing meaningful learning of the contents of organic chemistry, based on the methodology of Project-Based Learning. This is a qualitative research that uses bibliographical surveys and action research as approaches for the production of a Didactic Guide for Basic Education Chemistry teachers. This guide addresses the production of soaps with essential oils in a proposal for a project-based methodology for teaching organic chemistry. The research enabled a practical and theoretical interaction with the student’s previous knowledge, contributing to the student’s engagement in the teaching and learning process. Most students increased their level of learning with the development of the project. In addition, it was possible to perceive, on the part of the students, motivation and satisfaction in the process of teaching and learning Chemistry. In this way, when the experiments are developed together with the contextualization, that is, taking into account the partner culture and economic aspects of the student’s life, the learning results can be more efficient.